1993
DOI: 10.1007/bf00315511
|View full text |Cite
|
Sign up to set email alerts
|

Minimal biliary excretion and enterohepatic recirculation of metoclopramide in patients with extrahepatic cholestasis

Abstract: The biliary excretion and apparent oral clearance of metoclopramide (MCL) were determined after oral administration of 1 mg MCL/kg body weight to 10 patients suffering from extrahepatic cholestasis with nasobiliary tube for drainage of the common bile duct. A bilioduodenal endoprosthesis was subsequently fitted in 6 of these patients, i.e. the enterohepatic circulation was restored, and the apparent oral clearance was re-determined. Biliary excretion, comprising free MCL and the products of conjugation, accoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…In addition or as an alternative explanation of dicontinuous plasma levels the pH partitioning of MCL into the gastric juice may be dis cussed [ 16]. A third possibility, enterohepatic recirculation of MCL, may be ruled out based on former studies [17]. The wide variation of the plasma concentrations seen in our study has also been observed by others [18][19][20].…”
Section: Pharmacokinetics O F Oral Medium-dosed M Clsupporting
confidence: 62%
“…In addition or as an alternative explanation of dicontinuous plasma levels the pH partitioning of MCL into the gastric juice may be dis cussed [ 16]. A third possibility, enterohepatic recirculation of MCL, may be ruled out based on former studies [17]. The wide variation of the plasma concentrations seen in our study has also been observed by others [18][19][20].…”
Section: Pharmacokinetics O F Oral Medium-dosed M Clsupporting
confidence: 62%
“…As it has been shown that the N-O-glucuronide was also a major metabolite of metoclopramide in the urine [17], it can be assumed that part of the radioactivity excreted into urine was in the form of the 11 C-labeled N-Oglucuronide of [ 11 C]metoclopramide. The visibility of the gall bladder and duodenum on the PET images indicated that [ 11 C]metoclopramide also underwent, to a lower extent, biliary excretion [18].…”
Section: Discussionmentioning
confidence: 99%
“…The latter mechanism may be responsible for the high plasma concentration at 24 h in GD1 cattle in our study. concentration at 24 h after IV administration in GD1 cattle compared to WT cattle may cause an increase in the enterohepatic [28,32] or gasteroenteric circulation of metoclopramide [33].…”
Section: Discussionmentioning
confidence: 99%